THU0329 RED FLAG SIGNS OF SYSTEMIC SCLEROSIS ARE PREVALENT IN SUBJECTS WITH RAYNAUD'S PHENOMENONIN THE GENERAL POPULATION AND MAY BE A PROXY FOR LUNG INVOLVEMENT. (June 2019) - Abdulle, Amaal Eman; Brouwer, Elisabeth; Goor, Harry van; Westra, Johanna; Leeuw, Karina de; Mulder, Douwe J
Abstract : Background: Pulmonary involvement in systemic sclerosis (SSc) is very difficult to treat when diagnosed too late. Therefore, in order to optimally use "the window of opportunity" more attention should be given to the early identification of SSc. To the best of our knowledge, no studies exist that have structurally assessed the epidemiology of red flag signs and potential signs of pulmonary involvement in patients with Raynaud's phenomenon (RP). Objectives: To assess the prevalence of red flag signs in participants with RP. Moreover, we aim to investigate the occurrence of pulmonary signs and symptoms in participants with red flag signs. Methods: We retrospectively analyzed data from the LifeLines Cohort Study, which is a large population-based cohort study in the Northern parts of the Netherlands. A total of 74011 participants completed the connective tissue disease questionnaire. The presence of RP and red flag signs for SSc (i.e., puffy fingers, skin thickening distal, skin thickening proximal, and pitting scars) were obtained. Patients were classified as having red flag signs by the presence of at least one red flag sign in addition to RP. In addition, patient characteristics, self-reported pulmonary complaints, spirometry (screening for interstitial lung disease (ILD)), and uric acid (global screening for pulmonary arterial hypertension (PAH)) were also obtained. Three groups of participants were formed, namely: participants with RP and red flag signs (n=981), participants with RP without red flag signs (n=2946), and participants without RP and without red flag signs (n=70037). Results: The prevalence of red flag signs was 5 fold higher in participants with RP, as compared to the non-RP group (RP 25% [23.7-26.4], non-RP 5% [4.9-5.2], p<0.001). A total of 413(42.1%) of the participants with RP and red flag signs reported dyspnea, which was 1.5 fold higher than in those with RP but without red flag signs, and two-fold higher compared to participants without RP and without red flag signs (p<0.001). Moreover, dyspnea in rest and after exertion was more prevalent in participants with RP and red flag signs (p<0.001). In addition, participants with RP and red flag signs more frequently reported to suffer from pulmonary fibrosis (p<0.001, table 1 ), and had the lowest forced vital capacity, as compared to the other groups (p<0.001). Conversely, uric acid was not found to be elevated in participants with RP and red flag signs. Conclusion: This unselected cohort study from the general population demonstrates that the prevalence of red flag signs in subjects with RP may be as high as 25%. Potential signs and symptoms of pulmonary complaints are more prevalent in participants with RP who also reported red flag signs. This could indicate an increased risk of pulmonary involvement (i.e., ILD and PAH) in RP patients with red flag signs, although additional specific tests are mandatory to substantiate definite disease. Disclosure of Interests: Amaal Eman Abdulle : None declared, Elisabeth Brouwer Speakers bureau: Dr. Brouwer as an employee of the UMCG received speaker fees and consulting fees from Roche which were paid to the UMCG, Harry van Goor: None declared, Johanna Westra: None declared, Karina de Leeuw: None declared, Douwe J Mulder Grant/research support from: My University has received research grants for my research from: Boehringer Ingelheim and Actelion, Speakers bureau: My University has received speakers fee from: Sanofi